Hair Transplantation on the Baldness Region with Free Latissimus Dorsi Flap for Scalp Reconstruction: A Case Report - Man Wong Han; Jaeseong Moh; Ji-Ung Park (Archives of Plastic Surgery)
Scalp reconstruction, particularly with complex defects and infection risks, often favors microvascular free flaps. However, this method can result in unavoidable alopecia and undesirable aesthetics. This report describes a novel case where hair transplantation via follicular unit extraction (FUE) was applied to a free myocutaneous flap. A 44-year-old woman with Moyamoya disease suffered intracerebral hemorrhage a decade ago. Craniotomies and autologous bone cranioplasties led to wound dehiscence, with subsequent failed local flaps and skin grafts, and identification of a methicillin-resistant Staphylococcus aureus infection. The final scalp defect, measuring 13 × 9 cm, was reconstructed using a free myocutaneous latissimus dorsi flap. Nine years post-surgery, a 1,500-unit FUE hair transplantation procedure was conducted. The transplanted hair exhibited robust survival with adequate blood supply, achieving a satisfactory 80 to 85% survival rate at 12 months. This resulted in a notable improvement in the patient's external alopecia, with reported high levels of satisfaction. Free flaps offer a valuable method for scalp defect reconstruction; however, they may not ensure optimal aesthetic satisfaction due to alopecia. Nonetheless, successful FUE hair transplantation on a myocutaneous free flap can yield satisfactory aesthetic results.